A new approach to ‘on-demand’ treatment of lifelong premature ejaculation by treatment with a combination of a 5-HT1A receptor antagonist and SSRI in rats - Olivier, Jocelien D. A.; Janssen, Josien A.; Esquivel-Franco, Diana C.; de Prêtre, Stephen; Olivier, Berend (Frontiers in Neuroscience, 2023)
Lifelong premature ejaculation (PE) in men lacks an adequate on-demand pharmacological treatment. Although selective serotonin reuptake inhibitors (SSRIs) are used for PE they only work after chronic treatment, or if used on-demand, less adequately than chronic SSRI treatment. It has been shown that the addition of a behaviorally silent 5-HT1A-receptor antagonist to an SSRI can generate acute inhibitory effects on male rat sexual behavior. Atlas987 is a selective 5-HT1A-receptor antagonist with equal potency to displace agonist and antagonist binding to pre-and post-synaptic 5-HT1A receptors in rat and human brain. To investigate whether Atlas987 together with the SSRI paroxetine, a combination called Enduro, induces acute inhibitory effects on male rat sexual behavior, we tested Enduro in Wistar rats in a dose-dependent manner. We first tested the 5-HT1A receptor antagonist Atlas987 in 8-OH-DPAT induced serotonergic behavior in rats. Second, we tested Enduro in a dose-dependent manner in male sexual behavior. Third, we tested the effective time window of Enduro's action, and lastly, we measured the plasma levels of Atlas987 and paroxetine over an 8-hour period. Results showed that Enduro acutely and dose-dependently reduced the number of ejaculations and increased the ejaculation latencies. The behavioral pattern induced reflected a specific effect on sexual behavior excluding non-specific effects like sedation or sensoric-motoric disturbances. The time-window of activity of Enduro showed that this sexual inhibitory activity was at least found in a 1 to 4 hours' time window after administration. Plasma levels showed that in this time frame both Atlas987 and paroxetine are present. In conclusion, in rats, Enduro is successful in acutely inhibiting sexual behavior. These results may be therapeutically attractive as "on demand" treatment for life-long premature ejaculation in men.